INTERSUBJECTIVE RELATIONS WITH SCHOOLS DURING TOURISM PREPARATION (EDUCATION IN THE 21ST CENTURY, 2023)
In the current curricula of the secondary school and its standards, special attention is paid to the construction of the educational process, which ensures not only the acquisition of knowledge, but also the perception of the subjects, analysis, the formation of the generalization of the activities, phenomena among the schoolchildren, and most importantly, the application of that knowledge in practice. The whole educational process is built on interdisciplinary connections.From this point of view, tourism training, being one of the means of physical education for schoolchildren, with its diverse content and uniqueness can be considered the only aspect that provides various interdisciplinary connections with all subjects taught in school.The research aims to study the interdisciplinary connections between tourism training and general education subjects in the process of physical education.Interdisciplinary connections during the touristic school preparation of schoolchildren are presented.Further research will be directed to the development of the content and teaching methods of tourism preparation for 7th-9th grade students, as well as the introduction of a process of physical education.
Keywords: Keywords: Tourism training, interdisciplinary connections, knowledge, ability, schoolchildren.